2006
DOI: 10.1038/sj.cgt.7700979
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of tumor growth by intra-muscular transfer of naked DNA encoding adrenomedullin antagonist

Abstract: We have recently reported that the intra-tumoral injection of adrenomedullin (AM) antagonist (AMA; AM (22-52)) peptides significantly reduced the in vivo growth of a pancreatic cancer cell line in severely combined immunodeficient (SCID) mice. In the present study, we examined the effects of intra-tumoral and intra-muscular transfers of naked DNA encoding AMA on the in vivo growth of cancer cell lines. We demonstrate that these treatments induce the regression of a pancreatic cancer cell line and a breast canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…22), or intratumoral or i.m. transfection with an AMA-expressing plasmid (23), reduced microvascular density and growth of pancreatic tumors. These studies provide strong evidence for the angiogenic function of adrenomedullin.…”
Section: Introductionmentioning
confidence: 99%
“…22), or intratumoral or i.m. transfection with an AMA-expressing plasmid (23), reduced microvascular density and growth of pancreatic tumors. These studies provide strong evidence for the angiogenic function of adrenomedullin.…”
Section: Introductionmentioning
confidence: 99%
“…We showed that the intratumoral injection of AMA peptides suppressed tumor formation by human pancreatic cancer cells in nude mice (7) and that intramuscular injection of naked DNAencoding AMA almost completely suppressed tumor formation in mammary and pancreatic cancer cells in SCID mice (8). In the present study, we showed that OS-RC-2, an RCC cell line, expressed AM both under normoxia and hypoxia (data not shown).…”
Section: Discussionmentioning
confidence: 48%
“…The naked DNA-encoding AMA (AMA vector) (Fig. 1A) was injected intramuscularly using the ultrasound-microbubble method when the tumor size reached an average diameter of 4 mm (on day 13), as described previously (8). (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations